TRANSPARANSI DALAM PELAKSANAAN BANTUAN LANGSUNG TUNAI (BLT) DANA DESA - Tioma Roniuli Hariandja; Nanang Tri Budiman (Indonesian Journal of Law and Islamic Law (IJLIL), 2020)
Since May 2020, BLT DD has been implemented in Jember Regency, including Bangsalsari Village. However, in fact it’s couldn’t avoid a pros and cons, especially to recipients. So, it’s mean Bangsalsari must be respons and give right information public. Every regulation must referent to hierarchy of legislation, same as the BLT DD rules. However, we know law have the legal principles "lex specialis derogat legi generalis", Then regulation of Jember regency Number 8 of 2016 about Public Information Openness must be a reference to do programs of Jember regency. There are three elements that must be fulfilled in the implementation of BLT DD in Bangsalsari Village, in order to realize information transparency, namely publication, participation and reporting. Bangsalsari Village has fulfilled these three elements in the implementation of BLT DD.